Limits to Profit? A conceptual framework for understanding profit and sustainability - Jennifer B. Hinton (Post-growth Economics Network (PEN), 2022)
This article seeks to unpack how the generation of profit impacts social and ecological sustainability. It begins by framing profit as not necessarily sustainable or exploitative. Social and ecological inputs and impacts are necessary for economic processes and when social and ecological stakeholders are not compensated for their contributions to the process, they can be considered unpaid inputs and, thus, sources of profit. This often overlaps with exploitation of stakeholders, which occurs when one party financially benefits at the expense of another party. The paper examines how profit is generated by several common types of profit-seeking strategies. In doing so, a conceptual framework is developed that clarifies how profit-seeking strategies generate profit from four basic sources: efficiency gains; willing and informed contributions from social stakeholders; exploitation of social stakeholders; and exploitation of nature. The fact that there are a bounded number of sources of benign profit (and that there are limits to those sources) indicates that there are limits to profit. It also indicates that much of the profit generated today comes at the expense of people and nature, which helps explain the global sustainability crisis. This reveals some inherent perils of a profit-driven economy and implies that businesses in a sustainable economy should not pursue profit as an end. Thus, the paper adds clarity to the social and ecological sources and limits of profit. It also gives guidance for how profit should be treated in a sustainable economy.
Keywords: 330; Profit; Sustainable economy; Sustainable business; Tradeoffs; Exploitation; Value creation